Cover Picture: Manganese Silylene Hydride Complexes: Synthesis and Reactivity with Ethylene to Afford Silene Hydride Complexes (Angew. Chem. Int. Ed. 22/2017). Issue 22 (26th April 2017) - Price, Jeffrey S.; Emslie, David J. H.; Britten, James F.
Abstract : The reactions described by D. J. H. Emslie et al. in their Communication onpage 6223 ff. start with manganese and hydrogen, and sequentially introduce silicon and carbon, provided by the inukshuk in the foreground, a stone landmark used by peoples of the Arctic region, including northern Canada. In the background is "Hounds Tooth" in British Columbia (Canada), with two silylene hydride molecules climbing towards the core of the final product, a silene hydride complex.